Fear and Anxiety in Spreading Covid-19 Vaccine Hoaxes as Terror Communication - Ari Sulistyanto; Wa Ode Siti Nurhaliza; Salsa Salbilah; Fadia Shafa Aurellie (Budapest International Research and Critics University, 2022)
In dealing with the COVID-19 pandemic, vaccination is one of the essential strategies in ending the pandemic. However, amid vaccination efforts, various hoax information spread on social media with messages of fear and anxiety. Therefore, this study aims to reveal messages of fear, anxiety, and efficacy in spreading vaccine hoaxes through the theory of fear appeal. This study found that the most prominent communication fears were death and death threats through a content analysis approach. Anxiety communication is about vaccine impact, vaccine quality, vaccine content, and feelings of sin. Meanwhile, the efficacy communication relates to the vegetarian lifestyle, chemical treatment, and natural methods. Communication of fear and anxiety about vaccinations spread through hoaxes is intended to prevent people from vaccinating. The spread of vaccine hoaxes about fear and anxiety is part of terror communication with various labels created and also builds a discourse of distrust of the government. This research has implications for mapping vaccine hoaxes and can be a reference for the government in planning communications for the success of the vaccination program.